Pulse oximeter saturation targeting and oximeter changes in the benefits of oxygen saturation targeting (BOOST)-II Australia and BOOST-II UK Oxygen Trials - Stenson, B; Donoghoe, M; Brocklehurst, P; Davis, P; Juszczak, E; Marschner, I; Simes, J; Tarnow-Mordi, W (Elsevier, 2018)
Infants in the Australian and UK Benefits of Oxygen Saturation Targeting-II trials treated using revised oximeters spent more time within their planned pulse oximeter saturation target ranges than infants treated using the original oximeters (P < .001). This may explain the larger mortality difference seen with revised oximeters. If so, average treatment effects from the Neonatal Oxygen Prospective Meta-analysis trials may be underestimates.